Recruitment of Racial Minorities in Canadian Police Forces - Jain, Harish (Relations industrielles / Industrial Relations, 1987)
Reviewing existing police recruitment and selection policies across Canada, the author identifies systemic barriers faced by visible minorities in entering police forces and makes recommendations in order to increase the representation of such minority persons in Canadian police departments.